Magnetically-actuated hydrogel-based achiral planar microswimmers for SERS detection: In situ coprecipitation for continuous loading of iron oxide nanoparticles - Xiong, Junfeng; Zhang, Junkai; Zhong, Yukun; Song, Xiaoxia; Wang, Haoying; Cheang, U Kei (Frontiers in Bioengineering and Biotechnology, 2023)
Ultraviolet lithography is a very promising technology for the batch fabrication of biomedical microrobots. However, creating microrobots that can swim at low Reynolds number using biocompatible material while retaining strong magnetic properties and excellent biomedical functionality is a great challenge. Previously biomedical microrobots have either strong magnetic properties by using non-biocompatible nickel coating or good biocompatibility by using iron oxide particle-embedded hydrogel with weak magnetism, but not both. Alternatively, iron oxide nanoparticles can be coated on the surface of microrobots to improve magnetic properties; however, this method limited the usability of the microrobots’ surfaces. To address these shortcomings, this work utilized an in situ synthesis technique to generate high magnetic content inside magnetic hydrogel microswimmers while leaving their surfaces free to be functionalized for SERS detection. The hydrogel body of the magnetic hydrogel microswimmers was first prepared by Ultraviolet lithography. Then, the high content of iron oxide was achieved through a continuous in-situ coprecipitation cycle. Finally, SERS detection capability of magnetic hydrogel microswimmers was enabled by uniformly growing silver nanoparticles on the surface of the magnetic hydrogel microswimmers. In the motion control tests, the magnetic hydrogel microswimmers showed a high swimming efficiency and consistent synchronized motion. Furthermore, the magnetic hydrogel microswimmers were able to improve the detection efficiency of analytes under magnetic guidance.